2021
DOI: 10.1186/s13148-021-01078-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation biomarkers of myocardial infarction and cardiovascular disease

Abstract: Background The epigenetic landscape underlying cardiovascular disease (CVD) is not completely understood and the clinical value of the identified biomarkers is still limited. We aimed to identify differentially methylated loci associated with acute myocardial infarction (AMI) and assess their validity as predictive and causal biomarkers. Results We designed a case–control, two-stage, epigenome-wide association study on AMI (ndiscovery = 391, nvali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 41 publications
1
34
0
3
Order By: Relevance
“…The calibration and DCA plots also showed the very good fit of the model. Similar to previous findings (18,28), the model showed that methylation was an important molecular change in the development of AMI. Under the model, the 5 most important genes were FTO, WTAP, YTHDC1, IGFBP3, and CBLL1.…”
Section: Discussionsupporting
confidence: 87%
“…The calibration and DCA plots also showed the very good fit of the model. Similar to previous findings (18,28), the model showed that methylation was an important molecular change in the development of AMI. Under the model, the 5 most important genes were FTO, WTAP, YTHDC1, IGFBP3, and CBLL1.…”
Section: Discussionsupporting
confidence: 87%
“…Studies have revealed the complementary expression patterns of lipid metabolism, calcium regulation, and methylation of related genes in peripheral blood leucocyte samples of patients with MI (Agha et al, 2019). These CpGs sites and genes stress the correlation of ion regulation, lipid metabolism, and inflammation in the MI biological mechanisms (Fernández-Sanlés et al, 2021). Thus, the new DNA methylation sequencing technology can identify potential target sites related to the aberrant epigenetic regulation of MI (Koseler et al, 2020).…”
Section: Dna Methylation and MImentioning
confidence: 99%
“…Epigenetics data, especially DNA methylation, are a promising way to understand molecular mechanisms of diseases. A few studies have paid attention to the connection between DNA methylation and AMI [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%